Tell Barri/Kahat: la campagna del 2001 - Pecorella, Paolo Emilio (a3e8fbf2-3a0c-4b2b-801e-95e42774c172, 2004)
In the undulating plains of north-eastern Syria is the site of Tell Barri, identified with the city of Kahat. The archaeological sequence which has been brought to light stretches without interruption from the start of the third millennium up to the fourteenth century AD. This report records the results of the seventeenth excavation campaign, carried out by the group from the University of Florence and from the "Federico II" University of Naples. Layers from the end of the third millennium have been brought to light, the passage between the Mid- and Neo-Assyrian periods. In the palace of Tukulti-Ninurta II the reception hall was discovered. For the later periods, investigation has proceeded on the Great Defensive Wall of Parthian age, and on the large edifice in the lower city.